Dynamics of Microcystis surface scum formation under different wind conditions: the role of hydrodynamic processes at the air-water interface - Wu, Huaming; Wu, Xingqiang; Rovelli, Lorenzo; Lorke, Andreas (Frontiers in Plant Science, 2024)
Due to climate change, Microcystis blooms occur at increasing frequencies in aquatic ecosystems worldwide. Wind-generated turbulence is a crucial environmental stressor that can vertically disperse the Microcystis surface scum, reducing its light availability. Yet, the interactions of Microcystis scum with the wind-generated hydrodynamic processes, particularly those at the air-water interface, remain poorly understood. Here, we explore the response of Microcystis (including colony size and migration dynamics) to varying magnitudes and durations of intermittent wind disturbances in a mesocosm system. The flow velocities, size of Microcystis colonies, and the areal coverage of the water surface by scum were measured through video observations. Our results demonstrate that low wind speeds increase colony size by providing a stable condition where Microcystis forms a scum layer and aggregates into large colonies at the air-water interface. In contrast, wind disturbances disperse scum and generate turbulence, resulting in smaller colonies with higher magnitudes of wind disturbance. We observed that surface scum can form rapidly following a long period (6 h) of high-magnitude (4.5 m s -1 ) wind disturbance. Furthermore, our results indicate reduced water surface tension caused by the presence of Microcystis, which can decrease surface flow velocity and counteract wind-driven mixing. The reduced surface tension may also drive lateral convection at the water surface. These findings suggest that Microcystis reduces surface tension, likely by releasing surface-active materials, as an adaptive response to various wind conditions. This could result in an increased rate of surface scum re-formation under wind conditions and potentially facilitate the lateral expansion of scum patches during weak wind periods. This study reveals new insights into how Microcystis copes with different wind conditions and highlights the importance of the air-water interface for Microcystis scum dynamics.